INFLUENCE OF MULTILATERATION SURVEILLANCE SYSTEM ARRANGEMENT ON THE TARGET LOCALIZATION - Konchenko, Inna M.; Yanovsky, Felix J. (Proceedings of National Aviation University (archive), 2009)
In this article accuracy of target localization in multilateration surveillance system is estimated with the help of two approaches. The first approach is based on using data processing algorithm for computing target position. The second one is done with the help of Cramer−Rao Lower Bound. Results of these two approaches at the same initial data are compared and analysis is done. The results are relevant for development and future implementation of prospective multilateration systems in Ukraine.